(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to know the role of Iraqi banks in promoting financial investment (the Industrial Bank of Iraq as a model) for the benefit of the various industrial, commercial and service investment sectors alike. The importance of the research lies in it being a practical model to demonstrate the amount of development and support for the field of financial investment and the reflection of the government’s will to finance this field. Vital because it has a direct impact on the progress and prosperity of the country. Statistical data extracted from the banking documents of the Industrial Bank, the Central Bank of Iraq, and the National Investment Authority were used for the purpose of conducting statistics, comparison, and inferences through research. The results showed a positive role for Iraqi banks in promoting financing of financial investment, as the results of the investment financing variables were positive and upward and commensurate with the trend. The government supports various investment sectors, and those with expertise have a major role in managing the various investment financing sectors. The research recommended several recommendations, including: 1- Benefiting from the return of financial resources to stimulate the economy by raising the growth rate by the National Investment Authority and reviving the economy through investment in vital sectors. 2- Preparing investment plans based on scientific foundations, reconsidering and simplifying procedures, and finding ways to attract investors and encourage investment